(untitled) (African Journal of Biomedical Research, 2024)
Inguino-genital swelling that are non-inflammatory may be hernias or hydroceles and are inheritable. This study aims to investigate dermatoglyphics as non-invasive screening tool for inguino-genital predisposition within families. Fingerprints of 27 affected children (AC) [25 males, 2 females], 34 parents of affected children [8 fathers, 28 mothers], 32 non-affected children (NAC) [22 males, 10 females], and 36 parents of non-affected children [6 fathers, 30 mothers] were obtained from the University College Hospital and Adeoyo Specialist Hospital, Ibadan, Nigeria. Data were analysed with Automated Fingerprint Identification System and STATA software (P≤0.05). In AC and their mothers and NAC and their mothers, arch was statistically significant in the right fingers (RF). In AC and their fathers and NAC and their fathers, the ulnar loop was statistically significant in RF. Absolute finger ridge count was significant in RF of AC and their fathers and NAC and their fathers. In minutiae, the bifurcation and double bifurcation were statistically significant in the left fingers (LF) of AC and NAC. In AC and their mothers and NAC and their mothers, opposed bifurcation was statistically significant in LF. In AC and their fathers and NAC and their fathers, double bifurcation, bridge, dot, and break were statistically significant in LF, lake was significant in both RF and LF. There were weak positive and negative correlations in the patterns and minutiae distributions between AC and their parents. This study may be used as a marker alongside other genetic markers to identify predisposition to inguino-genital swellings of non-inflammatory, hereditary origin